Rights of the elderly with reference to Malaysia: Islamic and western perspectives - Fauzi, Husna (2014)
By 2050, the number of older persons in the world is projected to exceed the number of young for the first time in history. The United Nations Committee on Economic, Social and Cultural Rights has identified the elderly as a vulnerable group and at risk to various forms of abuse and exploitation. Consequently, there has been an increased concern among the international community for the creation of an international convention on the rights of the older persons. Having an international convention tailored to the needs of older persons is seen as an essential tool in promoting and protecting the rights of the elderly. Considering the fact that the Malaysian elderly population has steadily increased over the years, it is essential to give special attention to the interests and rights of this special group of population. This paper provides an overview of the rights of the elderly from Islamic and western perspectives, with particular reference to the position in Malaysia. It analyses the status of the elderly persons in IslÉm by referring directly to the divine sources: Qur’an and Sunnah. It also discusses the status of the elderly within the framework of the international and regional human rights instruments and Malaysia's commitments to protect and promote the rights of the elderly. Looking into the legislative and policy provisions directed towards the protection of the rights of the elderly, there is a need to adopt adequate measures to safeguard the rights and interests of the Malaysian elderly.